Development of an Arduino Based Electric Cooker Timer System - Oyedeji, Ajibola Oluwafemi; Oni, Abiola P.; Onaifo, Frank; Alao, Peter O. (Universitas Andalas, 2020)
The emerging trend in the world of semiconductor integration has brought about so many opportunities in the area of microcontrollers. This paper deals with the design and implementation of a microcontroller-based timer for home appliances using an Arduino microcontroller. This system is developed for the users to predetermine the time of operation of any home appliances using the electric cooker for implementation. The system is majorly comprised of the power supply unit, microcontroller unit, timer circuits and LCD display. The user can set any of the time given in the timer switch using keypad. The settings are stored in the microcontroller and the details are displayed in the LCD display. The appliance is controlled to run for the particular period set by the timer switch. The timer switch automatically makes the appliance off once the period is over. This system has been designed to be efficient, reliable and reduce energy wastage.